Management of recurrent aphthous stomatitis in HIV - Obradović Radmila R.; Kesić Ljiljana G.; Pejčić Ana S.; Bojović Marija D.; Petrović Milica S.; Stanković Ivana V.; Jovanović Marija G.; Popović Žana Z. (Medicinski fakultet i Klinika za stomatologiju, Niš, 2021)
Introduction: Today, human immunodeficiency virus (HIV) infection is often health problem. People with HIV are living longer and more of them are seeking care for the oral complications of this disease. This is the reason why the management of HIV infection is regular in the dental and medical everyday practice. Although HIV-related recurrent aphthous stomatitis (RAS) constitute a small percentage of oral lesions they are one of the most painful conditions of the oral cavity. The aim: is to point out the therapeutic possibilities and health improvement in people with HIV. Conclusion: Once a diagnosis of RAS is reached, the choice of a specific treatment modality is individual and the potential side effects of drugs should always be taken into account. It is important to reduce pain and achieve a prolonged remission.